Postural control as a risk factor for noncontact anterior cruciate ligament injury in youth female basketball and floorball athletes - Kattilakoski, O.; Leppänen, M.; Kannus, P.; Steffen, K.; Vasankari, T.; Kulmala, T.; Parkkari, J.; Pasanen, K. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The aim of this study was to investigate whether postural control was associated with an increased risk of future noncontact ACL injury in youth female basketball and floorball athletes. Data collection on 189 youth female basketball and floorball athletes was performed during a 3-year period. The modified Star Excursion Balance Test (mSEBT), single-leg drop-down test, and single-leg stance tests on a balance platform were used to measure postural control. In the mSEBT, performance in the anteromedial, medial, and posteromedial directions, as well as the corresponding composite score, were recorded. In balance platform tests, the mediolateral and anteroposterior velocity, velocity moment, and side length of a square representing 90% of postural sway were measured. Relative limb asymmetry and bilateral limb mean results for these variables were calculated and used as predictor variables in Cox regression analysis. Noncontact ACL injuries and individual exposure hours were prospectively recorded throughout the follow-up. Twelve noncontact ACL injuries occurred. Greater limb asymmetry in the posteromedial direction [HR 1.18 (95% CI 1.05-1.32)] and composite score [HR 1.17 (95% CI 1.01-1.36)] on the mSEBT were associated with an increased risk of noncontact ACL injury. No statistically significant associations were found in the other directions for the mSEBT or any of the balance-platform-generated variables. Dynamic postural control, measured by limb asymmetry in the mSEBT, was associated with future ACL injury. Prevention programs for noncontact ACL injury could benefit from exercises directed toward correcting limb asymmetries in dynamic postural control in youth female basketball and floorball athletes.